2018
DOI: 10.1002/ijgo.12545
|View full text |Cite
|
Sign up to set email alerts
|

Association of uterine leiomyoma and overactive bladder syndrome

Abstract: The study found a significant association between anterior and/or fundal leiomyoma and overactive bladder syndrome. The presence of uterine leiomyoma should be ruled out during the evaluation of overactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The location and size of leiomyomas also has been associated with worse lower urinary tract symp-toms, although this review demonstrates that this relationship is not well studied. One study found a significant association between anterior or fundal leiomyoma and overactive bladder symptoms, 6 and others have suggested that anterior-dominant leiomyomas and leiomyomas larger than 5 cm are associated with more severe symptoms. 7,59 However, there were insufficient data from this review to select interventions for pelvic floor symptom improvement or prevention based on size and location of leiomyomas.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The location and size of leiomyomas also has been associated with worse lower urinary tract symp-toms, although this review demonstrates that this relationship is not well studied. One study found a significant association between anterior or fundal leiomyoma and overactive bladder symptoms, 6 and others have suggested that anterior-dominant leiomyomas and leiomyomas larger than 5 cm are associated with more severe symptoms. 7,59 However, there were insufficient data from this review to select interventions for pelvic floor symptom improvement or prevention based on size and location of leiomyomas.…”
Section: Discussionmentioning
confidence: 98%
“…3 Pelvic floor symptoms are common in women with uterine leiomyomas; 56-64% of patients report urinary frequency, 35-59% report urinary incontinence (UI), and 40% report bowel symptoms such a fecal urgency and straining to have a bowel movement. [4][5][6][7] The precise relationship between leiomyo-mas and pelvic floor dysfunction is unclear. The close anatomic relationship of the uterus to the bladder and rectum as well as larger leiomyoma size resulting in mass effect on adjacent organs are postulated links between leiomyomas and pelvic floor dysfunction.…”
mentioning
confidence: 99%
“…[87][88][89] Pathology and illness LUTS onset in middle-aged and elderly women involves pregnancy, delivery, pelvic organ prolapse, menopause, estrogen deficiency, neurologic disorders, and aging. 1,5,6,75 Causative diseases with a high incidence of storage symptoms include urinary tract infection, OAB, stress urinary incontinence, pelvic organ prolapse, and interstitial cystitis, 1,[93][94][95][96][97][98] whereas causes of voiding symptoms and post-micturition symptoms include organic disease of the lower urinary tract such as bladder neck obstruction, bladder calculus, and urethral stricture, as well as age-related underactive bladder, disorders of the central nervous system, neurogenic bladder (seen following surgery for uterine cancer and rectal cancer), a history of urinary incontinence surgery, and cases associated with pelvic organ prolapse. 1,9,[99][100][101][102][103][104] Diagnosis is difficult in instances that cannot be inferred based on the patient's medical history, and urodynamic measurement is performed as needed in such cases.…”
Section: The Epidemiology Of Flutsmentioning
confidence: 99%
“…In addition, there seems to be a significant association between anterior and/or fundal leiomyoma and OAB. For this reason, the presence of uterine leiomyoma should be taken into account in women affected by overactive bladder [18][19][20][21].…”
mentioning
confidence: 99%